Synthesis, Physical Properties and Memory Device Application of a Twelve‐Ring Fused Twistheteroacene. Issue 6 (17th February 2017) - Duan, Jingdan; Gu, Pei‐yang; Xiao, Jinchong; Shen, Xingxing; Liu, Xiaoyu; Yi, Yuanping; Zhang, Qichun
Abstract: Developing new organic conjugated materials for high density memory devices is highly desirable. In this research, a novel donor–acceptor‐type twelve‐ring fused twistheteroacene, 2, 7, 19, 24‐tetra‐ tert ‐butyl‐13, 30‐didodecyl‐9, 17, 26, 34‐tetraphenyl benzo[8′, 9′]triphenyleno[2′, 3′:7, 8]dibenzo[b, e][1, 4]dioxino[1, 2, 3, 4‐lmn]dibenzo[6′, 7′:10′, 11′]tetraceno[2′, 3′:5, 6][1, 4]dioxino[2, 3‐f][3, 8]phenanthroline‐12, 14, 29, 31(13 H, 30 H )‐tetraone (DPyN ) has been synthesized and characterized. It displays high thermal stability, possesses a broad absorption band centered at 510 and 538 nm, and emits red fluorescence in organic solvents. A solution‐processed memory device withDPyN as an active element shows an excellent memory performance with an ON/OFF current ratio of 10 3.46 :1 and a threshold voltage of −2.44 V. Abstract : Twist and shout : A novel twelve‐ring fused twistheteroacene (DPyN ) has been synthesized and characterized. The twistheteroacene displays excellent behavior in memory devices with an ON/OFF current ratio of 10 3.46 :1 and a threshold voltage of −2.44 V.